Analisis Motivasi Kinerja Pegawai Kecamatan Cibitung Menggunakan Metode Analytical Hierarchy Process (AHP) - Andrean, Okta Teza; Saepudin, Sudin; Irawan, Carti; Mupaat (Jurnal Algoritma, 2025)
This study aims to analyze the factors that influence the performance motivation of Cibitung Subdistrict employees using the Analytical Hierarchy Process (AHP) method with a total of 22 subdistrict employee respondents. The three main criteria analyzed include work environment, rewards, and leadership. Data were obtained through a paired comparison questionnaire, which was then processed using the AHP method to determine the priority weight of each criterion. The results show that leadership is the dominant factor (0.666), followed by rewards (0.601) and work environment (0.534). The Consistency Ratio (CR) value of 0.00086 indicates that the respondents' assessments are consistent. These findings are expected to serve as a basis for policy-making to improve employee performance in the environment.